2019
DOI: 10.3389/fonc.2019.00931
|View full text |Cite
|
Sign up to set email alerts
|

Double-Stranded DNA in Exosomes of Malignant Pleural Effusions as a Novel DNA Source for EGFR Mutation Detection in Lung Adenocarcinoma

Abstract: Background: Exosomes are cell-derived vesicles and bear a specific set of nucleic acids including DNA (exoDNA). Thus, this study is to explore whether exoDNA in malignant pleural effusions (MPEs) could be a novel DNA source for mutation detection of epidermal growth factor receptor (EGFR).Methods: In this study, 52 lung adenocarcinoma patients were enrolled, and EGFR mutation status was detected with tumor tissues as well as cell blocks and exosomes in MPEs. The sensitivity, specificity and consistency of EGFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 25 publications
3
30
1
Order By: Relevance
“…EV/EP DNA in other fluids represents additional avenues for accessing DNA biomarkers. In lung adenocarcinoma, fluid from malignant pleural effusions harboured EV DNA with EGFR mutations that reflected the tumour genotype more accurately than conventional cytology approaches 110 , 111 . A subsequent study found a broad array of tumour-derived mutations reflected in EV DNA isolated from pleural effusion supernatant 112 , further reinforcing this approach as a viable liquid biopsy option in lung cancers.…”
Section: Ev/ep Dna As a Disease Biomarkermentioning
confidence: 99%
“…EV/EP DNA in other fluids represents additional avenues for accessing DNA biomarkers. In lung adenocarcinoma, fluid from malignant pleural effusions harboured EV DNA with EGFR mutations that reflected the tumour genotype more accurately than conventional cytology approaches 110 , 111 . A subsequent study found a broad array of tumour-derived mutations reflected in EV DNA isolated from pleural effusion supernatant 112 , further reinforcing this approach as a viable liquid biopsy option in lung cancers.…”
Section: Ev/ep Dna As a Disease Biomarkermentioning
confidence: 99%
“…Exosomal DNA analysis allows the detection of tumor-specific mutations, which, in the case of heterogeneous solid tumors, can give a more accurate picture of tumor genetics overall than small tissue biopsies [46]. The presence of the mutated epidermal growth factor receptor (EGFR) alleles in exoDNA, especially mutations such as exon 19 Del and exon 21 L858R, characteristic of lung cancer cells, may be important when selecting patients for targeted therapy using a tyrosine kinase inhibitor [40,47]. It has also been shown that mtDNA present in fibroblastderived exosomes activates oxidative phosphorylation (OXPHOS) in breast cancer cells, which leads to resistance to hormone therapy in OXPHOS-dependent breast cancer [48].…”
Section: Composition Of Cancer Exosomesmentioning
confidence: 99%
“…This nucleic acid cargo may include a variety of noncoding RNAs including microRNA and long non-coding RNA (lncRNA), tRNA fragments, small-interfering RNAs, structural RNAs, small RNA transcripts and RNA-protein complexes. Other than different RNA species, exosomes also contain DNA which could represent the entire genome as well as the genomic mutations, making them excellent biomarkers [55][56][57][58]. In addition to chromosomal DNA, mitochondrial DNA has also been reported [59,60].…”
mentioning
confidence: 99%